Convergence Order of the Reproducing Kernel Method for Solving Boundary Value Problems. Issue 4 (3rd July 2016) - Zhao, Zhihong; Lin, Yingzhen; Niu, Jing
Abstract: In this paper, convergence rate of the reproducing kernel method for solving boundary value problems is studied. The equivalence of two reproducing kernel spaces and some results of adjoint operator are proved. Based on the classical properties of piecewise linear interpolating function, we provide the convergence rate analysis of at least second order. Moreover, some numerical examples showing the accuracy of the proposed estimations are also given.